Central Pulse Wave Velocity and Augmentation Index Are Repeatable and Reproducible Measures of Arterial Function - Sophie L. Russell; Mushidur Rahman; Charles J. Steward; Amy E. Harwood; Gordon McGregor; Prithwish Banerjee; Nduka C. Okwose; Djordje G. Jakovljevic (Health Science Reports)
Abstract Background and Aims Arterial function (specifically arterial stiffness) is an important cardiovascular risk factor. Pulse wave velocity (PWV) and augmentation index (Alx) are established indicators of arterial function. The present study aimed to evaluate the repeatability and reproducibility of PWV and Alx in healthy individuals. Methods Forty healthy participants (age 33 ± 11 years, 17 females) underwent resting supine PWV and Alx assessments. Measurements were made in triplicate and repeated 1 week apart. Alx was measured by brachial occlusion and PWV was measured from the carotid artery to the femoral artery via the tonometer‐oscillometric method. Repeatability and reproducibility were assessed using the intraclass correlation coefficient (ICC). Interoperator reproducibility was performed on 10 participants. Results The average values for week‐to‐week visits for PWV and Alx were 6.20 ± 0.91 versus 6.13 ± 0.91 ms−1 and 14.0 ± 11.8 versus 16.3 ± 12.2% respectively. For same‐day measurements, both PWV and Alx showed excellent repeatability (PWV: ICC = 0.96, 95% CI: 0.92–0.98, p < 0.01; Alx: ICC = 0.90, 95% CI: 0.84–0.94, p < 0.01) and interoperator reproducibility (PWV: ICC = 0.98, 95% CI: 0.93–1.00, p < 0.01; Alx: ICC = 0.93, 95% CI: 0.69–0.98, p < 0.01). Measurements were repeated 1 week apart and showed good reproducibility (PWV: ICC = 0.77, 95% CI: 0.61–0.87, p ≤ 0.01; Alx: ICC = 0.73, 95% CI: 0.73–0.86, p < 0.01). Conclusion PWV and Alx demonstrate excellent repeatability and good reproducibility. Considering these variables are noninvasive and easy‐to‐measure, arterial function assessment may have a role in routine clinical practice to facilitate risk stratification in cardiovascular diseases.